2011
DOI: 10.1186/1471-2458-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Intervention mapping for the development of a strategy to implement the insurance medicine guidelines for depression

Abstract: BackgroundThis article describes the development of a strategy to implement the insurance medicine guidelines for depression. Use of the guidelines is intended to result in more transparent and uniform assessment of claimants with depressive symptoms.MethodsThe implementation strategy was developed using the Intervention Mapping (IM) method for alignment with insurance-medical practice. The ASE behavioural explanation model (Attitude, Social Influence and Self-Efficacy) was used as theoretical basis for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
(36 reference statements)
0
32
0
Order By: Relevance
“…78 While intervention mapping has been proposed as a method for tailoring implementation strategies to identified barriers, 22,39 it has not been widely used, with a few notable exceptions. 79,80 …”
Section: Methods For Selecting and Tailoring Implementation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…78 While intervention mapping has been proposed as a method for tailoring implementation strategies to identified barriers, 22,39 it has not been widely used, with a few notable exceptions. 79,80 …”
Section: Methods For Selecting and Tailoring Implementation Strategiesmentioning
confidence: 99%
“…80 The purpose of the guidelines was to ensure that assessments of depression symptoms by physicians were transparent and uniform. Zwerver and colleagues 80 provide a detailed account of the intervention mapping process, which resulted in the development of a multifaceted implementation strategy.…”
Section: Methods For Selecting and Tailoring Implementation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Birrell et al [40] provided an age structure-based compartmental model with a Bayesian synthesis of multiple evidence sources to reveal substantial changes in contact patterns throughout the epidemic. Besides of the compartmental models, other mathematical models are also used to describe the transmission dynamics [3, 4247]. The chain binomial model was used to calculate the household secondary attack rates to measure the transmissibility of the 2009 H1N1 influenza pandemic by Lessler et al [44] and Klick et al [45].…”
Section: Introductionmentioning
confidence: 99%
“…Ferguson et al [3] and Cauchemez et al [42, 43] incorporated other factors, such as household risk, within-school risk, and community risk, in the study of infection spread and found out that younger age groups under 19 years old were more susceptible than older age groups. Jin et al [47] formulated an epidemic model of influenza A based on networks and calculated the basic reproduction number and studied the effects of various immunization schemes. However, this work required that the individual contact pattern be provided.…”
Section: Introductionmentioning
confidence: 99%